STRUKTUR DAN KUALITAS TELUR AYAM LOKAL KHAS DAYAK BAGI PENGEMBANGAN DAN PELESTARIAN PLASMA NUTFAH TERNAK UNGGAS - Suhardi Suhardi (Jurnal Peternakan, 2013)
Local chicken is a chicken typical Dayak native of East Kalimantan Province from Berau District, subdistrict Segah and developed by the Dayak Kenyah and Ga' ai. Typical Dayak good local chicken to be developed as free-range chicken layer. The purpose of this research was to determine the structure and composition of chicken eggs as well as the its typical for evaluating the quality and nutrient content. The study was conducted from December 2010 to April 2011 at Department of Animal Husbandry Faculty of Agriculture, University of Mulawarman. The material observed in this study were 100 local chicken eggs typical Dayak. The parameters observed included: egg weight, egg length, egg width, egg index, egg shell color, egg shell weight, egg shell percentage, weight of egg white/albumen, high egg white/albumen, percentage of egg white/albumen, weight of egg yolk/yolk, yolk height, percentage of egg yolk/yolk, yolk color, hough unit, grade/USDA score, egg hatchability and fertility. These results have shown that the average weight of a typical local chicken eggs was 34.49 ± 4.17 g. In addition, there were 46.86 ± 2.41 mm of egg length, 34.99 ± 2.03 mm of egg width, 1.34 ± 0,07 of egg indices, 5.24 ± 0.98 g of egg shell weight, 15.19 % of egg shell percentage , 14.78 ± 2.39 grams of weight of egg white/albumen, 8.36 ± 1.08 mm of high egg white/albumen, 42.85% of, the percentage of egg white/albumen, 11.7 ± 2.42 g of the egg yolk/yolk, 19.71 ± 1.19 mm of egg yolk egg, 33.92% of the percentage of egg yolk/yolk, 98.17 ± 4.64 Hought unit of yellow dark yellow eggs, 12 score of 8,80% egg hatchability of grade/USDA, and 100% of fertility. Based on the findings, it is concluded that local chickens typical Dayak has a potensial for egg production.